GE_GERICHTE P/4953/2025 vom 20. März 2025 - GE Cour de justice (2025)
ORDONNANCE DE NON-ENTRÉE EN MATIÈRE;VOL(DROIT PÉNAL);USURPATION D'IDENTITÉ;CONTRAINTE(DROIT PÉNAL);SOUPÇON;DROITS STRICTEMENT PERSONNELS | CPP.310.al1.leta; CP.139; CP.179decies; CP.181; CPP.106.al3